استغالل األراضي الفالحية على ضوء القانون رقم 03 - مكدور النوي -- ضيف فاتن (المسيلة, 2023)
The subject of the agricultural land concession contract occupies an important and important place in Algerian legislation due to the desired objectives in preserving national property and agricultural lands, as it would contribute to the advancement of the agricultural sector and make it an alternative to hydrocarbons in the take-off of economic development and the concession is a new system in the real estate policy pursued since independence, so the Algerian legislator gave it great importance in the provisions that regulate it, by strengthening the supervisory role of state bodies in the exploitation of agricultural land, and enshrined the right Restitution of agricultural land in case of breach by the concessionaire of the obligations incumbent upon him
Keywords: الاراضي الفلا حية - القانون رقم 03 - عقد الامتياز - العقار الفلاحي - المستثمرات الفلاحية